Stability and convergence of N-body simulations for galaxy formation - Onions, Julian (2016)
Galaxy formation is still a current topic in astronomy. An important tool to understanding it is through simulation, which allows galaxies to be studied from all angles and across time. It allows us to explore the gap between observation and theory, but only if the results are sufficiently accurate. In this thesis I look at the majority of the simulation pipeline from running through the various stages of analysis, and some of the limits of their accuracy, and the fidelity of the subsequent analysis tools.